Дослідження ділянки Р-25 в Ольвії 2008 р. - Крапівіна, В.В.; Буйських, А.В. (Археологічні дослідження в Україні, 2009)
This publication is devoted to the main results of excavations on sector R-25 in Olbia in 2008, which continued the works of 2007. The area of newly added parts covered 190 м2. The Main Street of Olbia to the west from the main part of the sector was investigated, and opening of the layer to the east from the southern part of the defensive wall of the 2nd—3rd c. AD was begun. Excavations were also ongoing at the southern part of the sector on the area of more than 700 м2. Building ruins of the end of the 3rd through the 4th c. AD, the 1stand the 2nd c. AD, and the last quarter of the 6th through the 5th c. BC were investigated.